2018
DOI: 10.1002/ajcp.12243
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Housing and Shelter among People with Histories of Unstable Housing in three Cities in Canada: A Qualitative Study

Abstract: Housing is a key social determinant of health that contributes to the well-documented relationship between socioeconomic status and health. This study explored how individuals with histories of unstable and precarious housing perceive their housing or shelter situations, and the impact of these settings on their health and well-being. Participants were recruited from the Health and Housing in Transition study (HHiT), a longitudinal, multi-city study that tracked the health and housing status of people with uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…Moreover, an even larger number of individuals are vulnerably housed, living in precarious or sub-standard housing [2,3]. In Canadian cities, homeless and vulnerably housed individuals are concentrated in low-income, urban areas, where the majority of shelters, marginal housing, and associated health and social services are located [4,5]. Research with homeless and vulnerably housed individuals living in these areas has found that experiences of being either homeless or housed tend to be transitory, rather than stable life contexts [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an even larger number of individuals are vulnerably housed, living in precarious or sub-standard housing [2,3]. In Canadian cities, homeless and vulnerably housed individuals are concentrated in low-income, urban areas, where the majority of shelters, marginal housing, and associated health and social services are located [4,5]. Research with homeless and vulnerably housed individuals living in these areas has found that experiences of being either homeless or housed tend to be transitory, rather than stable life contexts [6].…”
Section: Introductionmentioning
confidence: 99%
“…The researchers did not find a statistically significant difference in the participants' social inclusion after they were housed for a year (Tsai et al, 2012). Similarly, a study by Sylvestre et al (2018) found that when participants (N=64) with precarious housing histories were housed, it resulted in isolation for some and put them at risk for re-entering homelessness because their need for support went unrecognized (Sylvestre et al, 2018). The researchers recommend conducting further research into specific interventions that could specifically target formerly homeless peoples' sense of social inclusion.…”
Section: Social Inclusion Homelessness and Povertymentioning
confidence: 92%
“…Throughout the related academic literature, environmental stress exposure exacted upon residents of public housing has only been studied from a social qualitative perspective, with residents reporting experiences of noisy, dirty, small, isolated and pest-infested housing conditions within housing and shelter developments in Canada. This particular study focused on the built environmental quality of individual public housing units (Sylvestre, 2018). This current study will focus more specifically on the neighbourhood environmental exposures inflicted upon residents of public housing, as geographic location is a key known determinant of environmental exposure to social and physical stressors, which are likely to affect health (Poulter et al, 2015).…”
Section: Background Informationmentioning
confidence: 99%